Perancangan Sistem Absensi Pegawai Berbasis Web Menggunakan Mapping Koordinat: Studi Kasus : BAWASLU Kota Surabaya - Nuris Sayyidatul Fatimah; Umi Chotijah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The development of advanced technology makes everything complicated easier, such as attendance that can be accessed online. Attendance data is needed by companies and organizations that can be used to support the provision of salaries, awards, and employee performance reporting. With the advancement of technology, many companies have implemented an online attendance system to facilitate the processing of employee attendance data, but the system can be used anywhere and makes it possible to find out employees who skip work. In certain cases, employees can take attendance at home even though they do not come to work, skip work or are late. This raises new thoughts for the author to build an online attendance system based on location coordinate mapping, where there is a time and coordinate map that shows the position of the employee displayed on the system, when absent and the reason for the employee's absence so that it can be anticipated to avoid employees who commit attendance fraud. The purpose of this research is to assist companies in overcoming attendance problems by building an online attendance system to overcome the problem of attendance of all employees and organizing all incoming data neatly and structured so that it is easier to summarize data information..